Modelling of Milk Absorption Characteristics of Popped Gorgon Nut (Euryale ferox) - Jha, S N; Sharma, Rajiv (Journal of Agricultural Engineering, 2010)
The milk absorption kinetics of popped gorgon nut was studied at different soaking temperatures (30, 50, 70 and 90 degree C) and time interval of 5s up to 90 seconds. Nine model equations for each measured parameter viz milk absorption (g/g dry matter) and geometric mean diameter (mm) were fitted and compared using their coefficients of determination (RÂ²), root mean square error (RMSE) and chi square (cÂ²) to estimate the best fit. The quantity of milk absorbed was higher at 30 degree C than at any other soaking temperatures studied. The rate of absorption was initially much pronounced, and got declined at later stage. The geometric mean diameter increased linearly at all the soaking temperatures and time. The effect of temperature and time, individually or in combination (interactions) thereof, significantly affected the absorption characteristics of popped gorgon nut.